Rotational stiffness determination of the semi-rigid timber-steel connection - Gečys, Tomas; Daniūnas, Alfonsas (Journal of Civil Engineering and Management, 2017)
In this research, the component method implementation for determination of the rotational stiffness of timber-steel connection is shown. Component method is one of the most commonly used methods for determination of the bending moment-rotation relation which later may be used in the practical analysis of the connection. The component method is not widely used for the analysis of the semi-rigid timber connections. There are only several investigations previously done on the component method implementation for the timber connections and most of them are based on only one basic component, i.e. timber compression or glued-in steel rod in tension. This article presents a new investigation of rotational stiffness determination algorithm of the semi-rigid timber-steel connection, which is based on the component method. The component method’s mechanical model of the connection combines all components which have influence on the rotational stiffness of the connection. The analysed timber-steel connection is subjected to pure bending. Stiffness coefficients of the steel part components are determined according to the Eurocode 3: design of steel structures Part 1-8: Design of joints. The timber part components are derived from the full-scale laboratory experiments and finite element modelling results, presented in the previous publications of the authors. The presented rotational stiffness determination results are well in line with the experimental and finite element modelling results, published in the previous publications.